The position of political parties from the internal events of Kurdistan Region Iraq 1991-1992 - Botany, Abdalfatah A.; Yousef, Khalat M. (Humanities Journal of University of Zakho, 2014)
The parties and movements of political Islam has got a lot of caring recently in Iraq as general and especially in Kurdistan after March 1991 uprising which was considered a great historical turn for existing and growing of Islamic movements and parties with different aims. However there are common factors between them but each one has it’s own speech diligence, and attitude which are all differed towards the political and social cases. In addition to that the political Islam was diseased with duality in attitudes which took on obvious totalitarian and political style which avoid them to determine there political attitude wether it’s religious or political yet they offend them both.The political Islam in Iraqi Kurdistan didn’t try to build a special situation for them within the social texture, but they took a part in a struggle with libral and nationalist parties as enter to change in order to take legitimacy and authority.This attitude appeard before and after the elections of Kurdish parliament at 1992 this attitude had a grisly effect and their situations in general for along period because they didn’t succeed to get the determined rate of voice which led to be sent off in participating within government.The parties and movements of political Islam tried to take Islam as a religious ideology in dealing with politics, but according to their form and content they are just political powers have their own political programmes and agendas.